COMPUTATIONAL EVALUATION OF CRITICAL WEAR LIMITS IN FORKLIFT FORK ARMS USING THE FINITE ELEMENT METHOD: TOYOTA 5FD70 CASE STUDY - Aminuddin; Rasyid Ridho Harahap; Oloan Oloan; Arif Rahman Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Forklift fork arms are critical load-bearing components that experience progressive thickness reduction due to operational abrasion. Indonesian Ministry of Manpower Regulation No. 08/2020 and ISO 5057:2022 require fork withdrawal when blade thickness is reduced to 90% of its original value. However, conventional inspection does not explain the continuous evolution of structural safety margins. This study evaluates the safety margin degradation of Toyota 5FD70 forklift fork arms under three wear scenarios using linear static Finite Element Method (FEM). The model geometry was developed from dimensional data in a certified inspection report. The material was modeled as AISI 4140 quenched and tempered steel with a conservative yield strength of 850 MPa. Numerical validity was checked through a mesh convergence study, reaching a final deviation of 1.98%. The results show that all static scenarios remain in the elastic regime, with Safety Factors of 1.745 at 0% wear, 1.759 at 5% wear, and 1.607 at 10% wear. A dynamic projection at 10% wear with a Dynamic Amplification Factor of 1.30 reduced the Safety Factor to 1.235, which falls into the marginal zone. These findings support the 10% wear limit as an early-warning threshold for risk-based forklift fork integrity management.